Die illuminierten Handschriften, Inkunabeln und Frühdrucke der Oberösterreichischen Landesbibliothek in Linz. Handschriften und frühe Drucke 1440–1540 (Tafeln und Register) - Hranitzky, Katharina (2018)
The present catalogue comprises detailed descriptions of approx. 90 illuminated manuscripts and early printed books from the collection of the Upper Austrian State Library in Linz. It focuses on the art-historical classification of the presented items for which the in-depth analysis of the books’ and fragments’ decorations constitutes the main basis. Through its many findings on the origin of the described works the catalogue can be regarded as a major contribution to the research on book-illumination and book-production in the late Middle Ages; furthermore it provides the reader with a large number of newly discovered historical data. Text see: http://e-book.fwf.ac.at/o:1160